Analysis of Almond Milk Quality at ABC MSME Yogyakarta - Yasmin, Annisa; Rahmadhia, Safinta Nurindra; Putri, Soraya Kusuma (Universitas Ahmad Dahlan, 2022)
Milk is a secretion from mammals that has a function as a source of nutrition. The presence of lactose in milk causes some to be deprived of milk because of lactose allergies. Dairy product for those who are allergic to milk is to consume vegetable milk, such as almond milk. The almond milk produced by Micro Small and Medium Enterprises (MSME) ABC is raw almond milk, which have short shelf life. Quality analysis is a step made to achieve and maintain the desired standards of taste, odour, color and texture. This study contribution to investigate the quality of almond milk after five days of storage. In MSME ABC, quality analysis is done by sensory test and compared with the quality standards set by MSME ABC. The quality of the almond milk analysis takes five days, with three different batches. Data retrieval methods conducted with secondary and primary data. After analysis, obtained data of almond milk on day 5 of storage was devalued. The conclusion of the observations made is that almond milk changes in flavor, color, scent and texture parameters after 5 days of storage.